Effective multi-functional biosorbent derived from corn stalk pith for dyes and oils removal. (June 2021) - Peng, Dan; Cheng, Shuping; Li, Huosheng; Guo, Xuetao
Abstract: In this study, malic acid-modified corn stalk pith (MA-CSP) was prepared as an environmentally friendly multi-functional bio-sorbent for adsorbing of dyes and oils. The sorption capacity of the MA-CSP for single and binary dyes is 328.46 mg/g - 566.27 mg/g. In addition, the MA-CSP also had good sorption for lubricating oil, soybean oil, diesel oil, and isopropyl alcohol, which were 37.2 g/g, 44.1 g/g, 33.8 g/g, and 29.3 g/g, respectively. Physical and statistical models were used to analyze the adsorption behavior of methylene blue (MB) and crystal violet (CV). And its sorption behavior for dyes was also affected by the co-existing salts in water. The sorption mechanism of the dye was mainly electrostatic attraction and hydrogen bonding action. The sorption of oil was primarily via the role of van der Waals force and hydrophobic interaction. The MA-CSP, as an eco-friendly, economical and eﬃcient multi-functional sorbent, holds promise for effective dyes and oil removal from contaminated water, and its application in other fields is also highly anticipated. Graphical abstract: Image 1 Highlights: Malic acid -modified corn stalk pith (MA-CSP) was synthesized as sorbent. MA-CSP had an effective adsorption performance on dyes and oils. Single and binary adsorption behaviors of dyes on MA-CSP was investigated. Classical and statistical modeling were used to study adsorption mechanism. Dye antagonistic adsorption was associated with statistical physics parameters.